Comparative Study of Strain and In-plane Electric Field Effects on Valley Polarization in the Magneto-optical Absorption Spectrum of a Borophene Monolayer - Quang, Doan Minh; Hue, Mai Thi; Thuy, Nguyen Thi; Thi Tho, Ta (VNU Journal of Science: Mathematics - Physics; Vol 41 No 4DO - 10.25073/2588-1124/vnumap.5017, 2025)
Borophene allotropes possess a variety of captivating physical properties, making them promising for numerous applications in practical devices. In this study, we theoretically explore the magneto-optical absorption of an  borophene monolayer subjected to an optical field and a perpendicular static magnetic field considering the combined effect of an in-plane electric field and mechanical strain. The magneto-optical absorption coefficient is calculated using perturbation theory, assuming a degenerate electron gas at low temperatures. The obtained results indicate that valley polarization in the optical absorption coefficient can only be achieved when the in-plane electric field and/or strain is applied to the system. The valley polarization varies gradually with the electric field and becomes significant only at high electric field strengths. On the other hand, the valley polarization is highly sensitive to strain. For the  valley, the absorption spectrum shows a red (blue) shift, with the intensity of the absorption peaks increasing (decreasing) as the strain becomes stronger. Additionally, the valley polarization strongly depends on the external magnetic field and the incident photon energy. For the given values of electric field and strain, as the external magnetic field increases, the polarization weakens. The above observations suggest that the combined effects of the factors on the valley polarization need to be considered systematically. The present results are significant for the application of strain and electric field engineering in valleytronics and flexible optoelectronic devices.